5 MODEL TEORITIK PRESTASI AKADEMIK SISWA KELAS UNGGULAN SMPN SE KOTA MALANG - Navion, Febranti Putri (Universitas Nusantara PGRI Kediri, 2016)
ABSTRACT This study aims to test empirically the theoretical models of student achievement excellent class and influence the efficacy of academic self-esteem, skills set goals, and creative thinking on student achievement excellent class in SMPN Malang, in terms of efficacy academic self-esteem, skill set goals, and creative thinking. Data was collected using methods Causal Relationship Study and analyzed using path analysis. The sample was featured grade students Malang number of 141 students, drawn by purposive random sampling. The results showed that the theoretical models of student achievement is not fully proven. Academic self-efficacy directly influence significantly to academic achievement, while the variables of self-esteem, setting goals skills and creative thinking have no direct impact significantly to academic achievement. Furthermore, self-esteem and skills to set goals affect academic self-efficacy. Key words: Academic self-eficacy, self-esteem, creative thingking skills to set goals, academic achievement